Impact of School Drop-out of Secondary School Students on Social Development in Pong Tek Commune, Romdoul District, Svay Rieng Province - Mardy Serey; Chhun Hong; Sochorda Youk; Sreynoch Mom; Boren Tham (Yayasan Pendidikan Genlita Indonesia, 2024)
Cambodia faces a significant challenge in developing a high-quality, capable, and productive workforce to meet the demands of its growing socio-economic development. However, many students dropped out of secondary and high school during the year. This study aims to investigate the impact of school drop-out among secondary school students on social development in Pong Tek commune, Romdoul district, and Svay Rieng province, Cambodia. The research methodology involved conducting interviews with 60 teachers who personally taught students at Hun Sen Pong Teuk High School. The result showed that some secondary school students still struggle with their studies. They have the highest travel expense deficit at 68%, lack study materials at 35%, and struggle to purchase clothes at 21%. The key factors that cause students to drop-out include internal factors (health and fitness, carelessness) and external factors (poverty, employment, late enrollment, violence, migration, distance from home to school, and social concerns). These student drop-out have a significant impact on social development, leading to issues such as illiteracy, job challenges, and a shift towards vocational training. In conclusion, many students drop-out of school for personal and social reasons, family problems, employment, and learning mismatch problems. After dropping-out of school, most of them lack adequate vocational training, which makes it difficult for them to find a job due to their hard work and low income. We recommend encouraging the students to pursue vocational training to enhance their skills, knowledge, and morality.